Similar Levels of Disease Severity Correspond to a Greater Burden of Illness in Women Compared with Men with Hidradenitis Suppurativa - Tonia Samela; Anna Dattolo; Giorgia Cordella; Valeria Antinone; Simona Mastroeni; Roberta Fusari; Luca Fania; Damiano Abeni (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)